Inflammatory Duodenal Polyposis Associated with Primary Immunodeficiency Disease: A Novel Case Report - Irfan Ali Shera; Sheikh Mudassir Khurshid; Mohd Shafi Bhat (Case Reports in Medicine)
Agammaglobulinemia is a rare form of B-cell primary immunodeficiency disease characterized by reduced levels of IgG, IgA, or IgM and recurrent bacterial infections. Agammaglobulinemia is most commonly associated with diffuse nodular lymphoid hyperplasia. Duodenal polyps are a rare entity; however, due to wide use of esophagogastroduodenoscopy, incidental diagnosis of duodenal polyps appears to be increasing. Although inflammatory duodenal polyposis has been reported in the literature, its association with common variable immunodeficiency has not been reported till date to the best of our knowledge. We report a case of a 59-year-old male with chronic symptoms of agammaglobulinemia associated with inflammatory duodenal polyposis.